I'm creating a program that simply show the effect of operator overloading, and I'm having a problem with *=. Code:

I can't place my finger on the problem. ob3 is supposed to have its current value (i) multiplied by the i field in ob2. ob2 is 59000, and the current value of ob3 is 74340. Multiplied together, it equals 4,386,060,000. After operator*= is called, ob3.i has 91,092,704 in it. At first I thought it was this:Code:#include <iostream> using namespace std; class Overload { int i; public: Overload() { i = 0; } Overload(int x) { i = x; } Overload(const Overload &ol) { i = ol.i; } int getI() { return i; } Overload operator+(int x) { Overload temp; temp.i = i + x; return temp; } Overload operator+(Overload ol) { Overload temp; temp.i = i + ol.i; return temp; } Overload operator+=(int x) { i += x; return *this; } Overload operator+=(Overload ol) { i += ol.i; return *this; } Overload operator++(int x) { i++; return *this; } Overload operator-(int x) { Overload temp; temp.i = i - x; return temp; } Overload operator-(Overload ol) { Overload temp; temp.i = i - ol.i; return temp; } Overload operator-=(int x) { i -= x; return *this; } Overload operator-=(Overload ol) { i -= ol.i; return *this; } Overload operator--(int x) { i--; return *this; } Overload operator*(int x) { Overload temp; temp.i = i * x; return temp; } Overload operator*(Overload ol) { Overload temp; temp.i = i * ol.i; return temp; } Overload operator*=(int x) { i *= x; return *this; } Overload operator*=(Overload ol) { i *= ol.i; return *this; } }; int main() { int y = 59, y2 = 100; Overload ob1, ob2(10), ob3(ob2); cout << "ob1's i: " << ob1.getI() << endl; cout << "ob2's i: " << ob2.getI() << endl; cout << "ob3's i: " << ob3.getI() << endl << endl; ob1 = ob1 + 76; ob2 = ob2 + y; ob3 = ob3 + ob2; cout << "ob1's i after adding (operator+) 76: " << ob1.getI() << endl; cout << "ob2's i after adding (operator+) y, with the value of " << y << ": " << ob2.getI() << endl; cout << "ob3's i after adding (operator+) ob2: " << ob3.getI() << endl << endl; ob1 += 25; ob2 += y2; ob3 += ob2; cout << "ob1's i after adding (operator+=) 25: " << ob1.getI() << endl; cout << "ob2's i after adding (operator+=) y2, with the value of " << y2 << ": " << ob2.getI() << endl; cout << "ob3's i after adding (operator+=) ob2: " << ob3.getI() << endl << endl; ob1++; ob2++; ob3++; cout << "ob1's i after adding (operator++) 1: " << ob1.getI() << endl; cout << "ob2's i after adding (operator++) 1: " << ob2.getI() << endl; cout << "ob3's i after adding (operator++) 1: " << ob3.getI() << endl << endl; ob1 = ob1 - 76; ob2 = ob2 - y; ob3 = ob3 - ob2; cout << "ob1's i after subtracting (operator-) 76: " << ob1.getI() << endl; cout << "ob2's i after subtracting (operator-) y, with the value of " << y << ": " << ob2.getI() << endl; cout << "ob3's i after subtracting (operator-) ob2: " << ob3.getI() << endl << endl; ob1 -= 25; ob2 -= y2; ob3 -= ob2; cout << "ob1's i after subtracting (operator-=) 25: " << ob1.getI() << endl; cout << "ob2's i after subtracting (operator-=) y2, with the value of " << y2 << ": " << ob2.getI() << endl; cout << "ob3's i after subtracting (operator-=) ob2: " << ob3.getI() << endl << endl; ob1--; ob2--; ob3--; cout << "ob1's i after subtracting (operator--) 1: " << ob1.getI() << endl; cout << "ob2's i after subtracting (operator--) 1: " << ob2.getI() << endl; cout << "ob3's i after subtracting (operator--) 1: " << ob3.getI() << endl << endl; ob1 = ob1 * 76; ob2 = ob2 * y; ob3 = ob3 * ob2; cout << "ob1's i after multiplying (operator*) by 76: " << ob1.getI() << endl; cout << "ob2's i after multiplying (operator*) by y, with the value of " << y << ": " << ob2.getI() << endl; cout << "ob3's i after multiplying (operator*) by ob2: " << ob3.getI() << endl << endl; ob1 *= 25; ob2 *= y2; ob3 *= ob2; cout << "ob1's i after multiplying (operator*=) by 25: " << ob1.getI() << endl; cout << "ob2's i after multiplying (operator*=) by y2, with the value of " << y2 << ": " << ob2.getI() << endl; cout << "ob3's i after multiplying (operator*=) by ob2: " << ob3.getI() << endl << endl; return 0; }

ob3 *= ob2;

Which would mean the problem would be the overloaded *= with an Overload argument. But i replaced it with

ob3 = ob3 * ob2;

And it yielded the same result. Can anyone see the problem, its driving me crazy. Thanks !